Keragaman Industrialisasi Pada Kebijakan Pemerintah - Dyah Ayu Puspita; Awang Adiat Maulana; Muhammad Yasin (Institut Nalanda, 2023)
Government policies play an important role in world industry. Industrial policy is about wise government decisions in its efforts to change sentiment between industry and other economic sectors in a meaningful way, related to the sector's contribution to the economy, response rate, and income per capita. This research is part of a descriptive qualitative research on the diversity of industrialization in Indonesian government policies using various sources.